Genetic diversity analysis of coloured upland rice germplasm using SSR markers, quantitative traits, and nutritional quality - Ahmad, Faiz (2014)
Rice (Oryza sativa L.) is a staple food for many people around the world. It contains high carbohydrate, which is as a source of energy. Currently, people are more concern about healthy food intake. Coloured rice is one of the alternatives for healthy diet because it has high nutritional value. In addition, coloured rice have antioxidants compound, such as polyphenols, carotenoids, and tocochromanols. These antioxidants have significant important health effect in human body. In this study, 42 selected coloured upland rice accessions were obtained from International Rice Research Institute (IRRI). There were collected from difference places around the world. To reveal the genetic diversity among the accessions, 25 short sequence repeated (SSR) markers were used in this study. Out of 25 SSR markers used in this study, only 21 were polymorphic. The polymorphic information content (PIC) value ranged from 0 (RM 338, RM 431, RM 118, RM 133) to 0.760 (RM 455). Mean of expected heterozygosity (He) was 0.470 and Shannon’s information index ranged from 0.380 to 1.660. From SSR markers, clustering analysis using JaccardSimiliarity Coefficient showed that all the accessions were clustered into 7 groups. The seeds among all accessions were planted in the glasshouse for multiplication, morphological and assessments of agronomical characteristic using randomized complete block design (RCBD) with 3 replications for each accession. The following parameters were collected: number of tiller per plant, number of panicle per plant, plant height, length flag leaf, panicle length, percentage of filled grain, percentage of unfilled grain, harvest index, yield per plant, 100 grains weight, days to flowering, days to maturity, length breath ratio of kernel, kernel length, chlorophyll content (SPAD reading) at 40 and 60 days. All data were analyzed by using SAS 9.2 software. Agro-morphological characters showed significant variation among all accessions. The heritability from 25 agro-morphological characters and nutrient content (macro & micro) in rice straw ranged from 56.52 to 99.31%. The nutrient contents (macro & micro) in rice grain varied greatly among accessions. The antioxidant activities for all rice accessions determined by 1,1- Diphenyl-2-picrylhydazyl (DPPH) radical scavenging effect method ranges from 31.85 to 98.45%. Based on the content of vitamin E (tocochromanols), the tocotrienol content was higher than that of tocopherol for all accessions selected. The selection of better rice accessions for future breeding program could be obtained using information from agro-morphological data, and nutritional status of the rice accessions.